Pendampingan Produksi Air Mineral Belik Bening sebagai Upaya Pemberdayaan Umkm di Desa Sahang, Kecamatan Ngebel, Kabupaten Ponorogo - Yafita Arfina Mu'ti; Rizeki Munatul Fadhilah (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to explore the role of Belik Bening Mineral Water business in supporting Small, Medium, and Micro Enterprises (UMKM) in Sahang Village, Ngebel Subdistrict, Ponorogo Regency. The research uses a qualitative approach with the Asset-Based Community-Driven Development (ABCD) model, employing methods such as interviews, observation, and documentation. The findings show that Belik Bening helps improve the local economy by creating jobs, providing affordable quality drinking water, and strengthening the UMKM sector by utilizing local potential. The production process follows hygiene standards, including steps like filtration, sterilization, packaging, and quality monitoring. Its marketing strategy is carried out in stages, starting with local distribution, then expanding to the Telaga Ngebel tourist area, and supported by the use of digital media. Although facing challenges such as limited capital, worker skills, and market competition, the business still has great growth potential because of the availability of water resources, community and village government support, and the potential of the tourism market. Therefore, Belik Bening has the possibility to become a village's outstanding product and a means of sustainable community empowerment.